LEGAL FORCE OF PERMA NO. 4 OF 2014 RELATING TO THE IMPLEMENTATION OF DIVERSION FOR CHILDREN AGAINST THE LAW (ABH) (CASE STUDY OF CASE NUMBER 14/Pid.Sus-Anak/2021/PN.Cbn) - Darisa, Mesya Nur Fadilla Oktaviani; Rahayu, Indah; Setiadi, Gyfari Farhan Nur; Henda, Rd.; Nurhaqi, Ari (Ridwan Institute, 2024)
The purpose of this study is to identify how the application of PERMA No. 4 of 2014 to diversion efforts and how the legal force of the law in the enforcement of diversion at the court level in order to achieve justice for children in conflict with the law (ABH). The research primarily utilized qualitative data derived from both primary and secondary sources. The primary data includes case files and court decisions related to Case Number 14/Pid.Sus-Anak/2021/PN.Cbn, as well as the legal text of OPREMA No. 4, while secondary data is obtained from literature reviews of law journals, books, and prior research. The data analysis is conducted using content analysis and the case study method, allowing for a comprehensive examination of how the COPREMA of 2014 has been applied in this specific legal context. The results of the author's research through an interview with Mr. Sukiran, S.H. as the Deputy Criminal Registrar of the District Court I B Cirebon on Tuesday, June 4, 2024 at 14.30 WIB, regarding different regulations related to the diversion in each law enforcement agency, among other things, it can trigger the smooth running and results of judicial decisions. A comparative analysis of cases where diversion was achieved versus those where it failed could provide deeper insights into how diversion attempts can be improved, especially for cases involving children who face significant legal and social challenges. Additionally, examining the impact of such legal frameworks on recidivism rates among juvenile offenders could offer practical recommendations for enhancing the juvenile justice system in Indonesia.